“Did You Notice That?” Theorizing Differences in the Capacity to Apprehend Institutional Contradictions - Voronov, Maxim; Yorks, Lyle (Academy of Management Review, 2015)
Over the past decade, institutional researchers have relied extensively on the premise that institutional contradictions are key drivers of institutional instability and institutional change. In this article we argue that apprehending institutional contradictions—that is, experiencing institutional arrangements as provisional and potentially changeable upon encountering the contradictions—is more problematic than typically acknowledged. Drawing on insights from constructive developmental theory, we develop an individual-level theory that seeks to explain the differences in people’s capacity to apprehend institutional contradictions. The resulting framework proposes that there are important differences among people with respect to the nature of their investment in institutional arrangements that correspond to the differences in both blockages and facilitators of apprehension. The framework contributes important insights to the study of embedded agency and inhabited institutionalism, as well as strategic change.